Osteomyelitis and Fracture Susceptibility: A Review of the Literature and Case Series of Surgical Treatment of Pathologic Calcaneal Fractures - Michael J. Hurst, DPM; Margaret Kedzie, DPM; Hannah J. Hughes, DPM; Patrick R. Burns, DPM, FACFAS; Jeffrey M. Manway, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases, 2023)
Introduction: Pathologic calcaneal fractures, often arising from osteomyelitis, present intricate challenges in orthopedic surgery. This paper explores the historical context, etiological factors, and evolving treatment approaches for these fractures, with a focus on the interplay between infection and compromised bone integrity. Methods: A retrospective analysis of four cases of pathologic calcaneal fractures complicating osteomyelitis, treated at the University of Pittsburgh Medical Center from 2017 to 2021, was conducted. The patients underwent debridement, external fixation, and long-term antibiotic therapy. A comprehensive literature review was conducted, encompassing all relevant papers discussing surgical treatment strategies for pathologic calcaneal fractures. Results: The case series reveals the complexities of managing these fractures. While external fixation stabilized the fractures and facilitated infection control, the outcomes varied. Some patients achieved fracture union and improved ulceration, while others experienced complications and, tragically, mortality due to underlying comorbidities. Discussion: Treatment modalities for osteomyelitis-related calcaneal fractures encompass debridement, external fixation, and tailored antibiotic therapy. Debridement is essential for infection control and wound preparation. External fixation provides stability, facilitates wound care, and allows for antibiotic delivery. Antibiotic therapy complements surgical interventions and targets the infection. However, challenges persist, including compromised overall health, persistent infection, and limited long-term outcomes. Conclusion: Pathologic calcaneal fractures complicated by osteomyelitis pose a formidable clinical challenge. Despite innovative approaches like the use of suture anchors and external fixation, achieving successful outcomes remains elusive. These cases often result in substantial morbidity and, at times, mortality due to the intricate interplay of infection, compromised bone quality, and comorbidities. Clinicians must balance aggressive intervention with a realistic assessment of the patient's overall health and prognosis. Further research and standardized treatment approaches are imperative to address the unique complexities of these cases and improve patient outcomes.